Devil in winter eaudiobook - Kleypas, Lisa (Wallflowers, 2021)
""I'm Sebastian, Lord St. Vincent. I can't be celibate. Everyone knows that."" Desperate to escape her scheming relatives, Evangeline Jenner has sought the help of the most infamous scoundrel in London. A marriage of convenience is the only solution. No one would have ever paired the shy, stammering wallflower with the sinfully handsome viscount. It quickly becomes clear, however, that Evie is a woman of hidden strength—and Sebastian desires her more than any woman he's ever known. Determined to win her husband's elusive heart, Evie dares to strike a bargain with the devil: If Sebastian can stay celibate for three months, she will allow him into her bed. When Evie is threatened by a vengeful enemy from the past, Sebastian vows to do whatever it takes to protect his wife . . . even at the expense of his own life. Together they will defy their perilous fate, for the sake of all-consuming love.